2002
DOI: 10.1097/01.asn.0000033463.58641.f9
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Na+-Dependent Dicarboxylate Transporter, NaDC-3, Translocates Dimethyl- and Disulfhydryl-Compounds and Contributes to Renal Heavy Metal Detoxification

Abstract: Abstract. The active transport of Krebs cycle intermediates, such as succinate, ␣-ketoglutarate, and citrate, is mediated by sodium-coupled transporters found in the luminal (NaDC-1) and basolateral plasma membranes (NaDC-3) of proximal tubule cells. This study used the two-electrode voltage clamp technique to examine steady-state currents associated with the influx of three sodium ions and one divalent dicarboxylate into oocytes expressing the sodium-dicarboxylate transporter from winter flounder kidney, fNaD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 46 publications
0
45
0
3
Order By: Relevance
“…The two dicarboxylates with the lowest affinities (3OHGA, GC) exhibited a potentialdependent K m , whereas unsubstituted and C2-substituted dicarboxylates showed K m values independent of membrane potential between −90 and −30 mV. The heavy metal chelator, 2,3-dimercaptosuccinate, also had a K m increasing with depolarization [22], suggesting that hNaDC3 has to perform a voltage-dependent step in interacting with compounds carrying a substitution at C3 or a double bond between C2 und C3. The maximal currents, I max , decreased in the order D-2OHGA>3OHGA=L-2OHGA>GA= adipate> GC>αKG.…”
Section: Discussionmentioning
confidence: 96%
“…The two dicarboxylates with the lowest affinities (3OHGA, GC) exhibited a potentialdependent K m , whereas unsubstituted and C2-substituted dicarboxylates showed K m values independent of membrane potential between −90 and −30 mV. The heavy metal chelator, 2,3-dimercaptosuccinate, also had a K m increasing with depolarization [22], suggesting that hNaDC3 has to perform a voltage-dependent step in interacting with compounds carrying a substitution at C3 or a double bond between C2 und C3. The maximal currents, I max , decreased in the order D-2OHGA>3OHGA=L-2OHGA>GA= adipate> GC>αKG.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to providing citric acid cycle metabolites for energy metabolism, NaDC3 also participates in the secretion of drugs and xenobiotics by providing glutarate and ␣-ketoglutarate to the organic anion exchangers OAT1 and OAT3, which are important for drug pharmacokinetics (9). The range of NaDC3 substrates also includes the clinically used heavy metal poisoning antidotes, such as succimer (10), and the antioxidant glutathione (11). NaDC3 is also important for the transport of N-acetyl aspartate in neurons and astrocytes, thought to contribute to osmoregulation in the brain (12).…”
mentioning
confidence: 99%
“…However, the significance of both routes is debated (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The sodium-dependent dicarboxylate transporter NaDC-3 has been implicated in the basolateral uptake of 99m Tc-DMSA from peritubular capillaries into proximal tubule cells (13). The mechanism by which 99m Tc-DMSA may be reabsorbed from the glomerular ultrafiltrate is unknown; however, studies have indicated that this route may contribute substantially to the renal uptake of the tracer (4,5,14).…”
mentioning
confidence: 99%